Respuesta :
6f-1 and 2f+ 4f +2-3 are equal. 2f +4f+2-3 is 17 at f=3 because
(2•3)+(4•3)+(2-3) =
(6+12)+(-1) =
(18)+(-1)=
17
Plug in what f equals for f in the equation and evaluate
I hope this helps.
(2•3)+(4•3)+(2-3) =
(6+12)+(-1) =
(18)+(-1)=
17
Plug in what f equals for f in the equation and evaluate
I hope this helps.

Answer:
Yes it is equivalent.
Step-by-step explanation:
In this case the only thing that you have to do to know if the two expressions are equivalent are put them on opposite sides of the equation like this:
6f-1= 2f+4f+2-3
When you simplify this you´ll end up with the next equation:
6f-1= 6f -1
In this case you can see that both expressions are equivalent because they are the same once you put them on opposite sides of the equation.